2013
DOI: 10.1038/ncomms3145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carbon dioxide and temperature on microRNA expression in Arabidopsis development

Abstract: Elevated levels of CO 2 and temperature can both affect plant growth and development, but the signalling pathways regulating these processes are still obscure. MicroRNAs function to silence gene expression, and environmental stresses can alter their expressions. Here we identify, using the small RNA-sequencing method, microRNAs that change significantly in expression by either doubling the atmospheric CO 2 concentration or by increasing temperature 3-6°C. Notably, nearly all CO 2 -influenced microRNAs are affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 55 publications
1
96
0
Order By: Relevance
“…Therefore, although an hd2d mutant has yet to be analyzed, it is conceivable that this gene might play a role in controlling v-6 ΔDE. The expression level of MIR172A also has been shown to respond to temperature, and this microRNA targets several APETALA2 domain transcription factors involved in temperature-sensitive processes such as flowering (May et al, 2013). There also is evidence that FAD2 is phosphorylated in soybean (Tang et al, 2005) and Arabidopsis (Durek et al, 2010) and that elevated temperature promotes the degradation of FAD2 isoforms via the ubiquitin-proteasome pathway (Tang et al, 2005).…”
Section: )mentioning
confidence: 96%
“…Therefore, although an hd2d mutant has yet to be analyzed, it is conceivable that this gene might play a role in controlling v-6 ΔDE. The expression level of MIR172A also has been shown to respond to temperature, and this microRNA targets several APETALA2 domain transcription factors involved in temperature-sensitive processes such as flowering (May et al, 2013). There also is evidence that FAD2 is phosphorylated in soybean (Tang et al, 2005) and Arabidopsis (Durek et al, 2010) and that elevated temperature promotes the degradation of FAD2 isoforms via the ubiquitin-proteasome pathway (Tang et al, 2005).…”
Section: )mentioning
confidence: 96%
“…The association of miRNAs with abiotic stress responses is now well established (Sunkar and Zhu, 2004; Jeong et al , 2011; May et al , 2013; Agarwal et al , 2015), but despite miRNAs being the key components of gene regulation during these stresses, the study of high temperature-responsive miRNAs is very limited in rice and other crops (Jeong and Green, 2013). Understanding miRNA expression and regulation during elevated temperature will help in better understanding the molecular pathways associated with high temperature response in the model monocot crop rice.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies have shown that the expression level of miR156 changes in response to growth temperature (Lee et al, 2010;May et al, 2013;Stief et al, 2014). miR156 levels regulate developmental transitions in plants, including the floral transition (Wang, 2014).…”
Section: Gwas and Qtl Analysis Identifies Loci Associated With Thermamentioning
confidence: 99%